2012
DOI: 10.1016/j.optcom.2011.10.037
|View full text |Cite
|
Sign up to set email alerts
|

THz optical pulses from a coupled-cavity quantum-dot laser

Abstract: Optical pulses are generated from a coupled-cavity quantum-dot (QD) laser consisting of a short QD-waveguide Fabry-Perot (F-P) cavity and three long external fiber Bragg grating (FBG) cavities. When the laser is biased at low operation current, the feedback from the external cavities dominates and laser pulses have a 1.01 THz repetition rate, determined by the equal frequency difference of the three FBGs. We are thus able to decouple the repetition rate of a mode-locked laser from the cavity length. With much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Using the In 0.32 Ga 0.68 As underlying layer, similarly uniform Qdots were observed with an average lateral size and height of 42 nm and 3 nm, respectively, and PL linewidth 64 meV centered at ~1.55 µ m. The improvement in Qdots size uniformity was ascribed to the different growth front, growth behavior of group III elements at the interface between Qdots and barrier, and the modulation in the strain field. Surprisingly, growth of nanostructures directly on AlInAs lattice matched matrix layer without any underlying layer show Qdots formation with slight elongation along [1][2][3][4][5][6][7][8][9][10] direction, as seen in Fig. 6(a), consistent with the results reported by Brault et al [23], while the elongation significantly reduced on InAlGaAs matrix layer (see Fig.…”
Section: Qdots On (100) Inp Substratesupporting
confidence: 89%
See 4 more Smart Citations
“…Using the In 0.32 Ga 0.68 As underlying layer, similarly uniform Qdots were observed with an average lateral size and height of 42 nm and 3 nm, respectively, and PL linewidth 64 meV centered at ~1.55 µ m. The improvement in Qdots size uniformity was ascribed to the different growth front, growth behavior of group III elements at the interface between Qdots and barrier, and the modulation in the strain field. Surprisingly, growth of nanostructures directly on AlInAs lattice matched matrix layer without any underlying layer show Qdots formation with slight elongation along [1][2][3][4][5][6][7][8][9][10] direction, as seen in Fig. 6(a), consistent with the results reported by Brault et al [23], while the elongation significantly reduced on InAlGaAs matrix layer (see Fig.…”
Section: Qdots On (100) Inp Substratesupporting
confidence: 89%
“…11. This was attributed to the lower step energy of InAs A steps (along [1][2][3][4][5][6][7][8][9][10]) than B steps (along [110]) and thus of the shorter diffusion length of In in the [110] direction. Furthermore, the effect of growth temperature did not significantly change the Qdot structural and optical characteristics which indicated that the effective diffusion length of the adatoms on the surface is limited by the presence of steps.…”
Section: Qdots On (100) Inp Substratementioning
confidence: 99%
See 3 more Smart Citations